The association between health financing and maternal and child health in Middle East and North Africa countries - Abdelgawad, Ahmed Tammam (AUC Knowledge Fountain, 2015)
Improving maternal and child health outcomes for women and children is a critical step to achieve the MDGs; however it requires sufficient funding to implement proven quality interventions. The aim of the study is to investigate the relationship between the different health care financing options cross the Middle East and North Africa “MENA" countries and the maternal and child health outcomes. Our main argument is that: Can different health care financing strategies affect Maternal, Neonatal and Child health? If yes, How?. This study is based on a cross sectional analysis of twenty one states from MENA region between 2009 and 2013 exploring the three dimensions of the maternal and child health outcomes namely a) Infant mortality b) Maternal mortality and c) Child health. Correlation between financial and maternal and child health indicators as well as linear regressions was carried out to investigate the relationships between the maternal and child health indicators and health spending consequently health system financing strategy. The findings of this study indicate that more spending on health is highly associated with positive maternal and child health outcomes namely reduction in infant and child mortality. Our results also indicate that the improvements in government effectiveness in regards to government health spending is accompanied with higher maternal and child health outcomes. Thus, increasing government expenditures is likely to lead to better improvements of health outcomes if it is accompanied by the right policies and institutions, which was the case of the first group of countries in MENA region.